Analysis Of The Impact Of The Barito Market Relocation On The Economic Stability Of Motorcycle Spare Part Traders In Semarang City - Efendi, Hafiz Afrizal (Semarang State University Undergraduate Law and Society Review, 2025)
Barito Market in Semarang City serves as a central hub for motorcycle spare parts trade, playing a strategic role in the local economy. The market’s relocation, initiated by the local government, aimed to enhance comfort and orderliness in accordance with Semarang City Regional Regulation Number 9 of 2013 on the Management of Traditional Markets. This study aims to examine the impact of the relocation on the economic stability of motorcycle spare parts traders. The research employed a qualitative method with an empirical juridical approach, utilizing data collection techniques such as interviews, observation, documentation, and literature review. The results show that the relocation initially caused a decline in traders’ turnover due to customers’ unfamiliarity with the new location. However, in the medium term, traders who adapted well began to experience an increase in customers and income. Furthermore, the relocation created a more equal competitive environment among traders, due to a more organized market layout. In conclusion, while the relocation posed initial challenges for traders, in the long term, it has the potential to support business sustainability if backed by responsive regulations and adaptive strategies from market participants.